An atom probe study of the distribution of rhenium in a nickel-based superalloy - Warren, P; Cerezo, A; Smith, G (1998)
The beneficial effect of Re on the high temperature properties of single-crystal nickel-based superalloys has resulted in a steady increase in the levels of Re used in these alloys. This paper reports an energy compensated 3D atom probe investigation of superalloy RR3000 after high temperature testing. Clear experimental evidence of pileup of Re solute atoms in the gamma matrix ahead of the growing gamma' particles was observed for both large primary gamma' rafts and also small secondary gamma' precipitates. The effect of the observed bow wave of Re on the rate of microstructural coarsening during precipitate growth is discussed. (C) 1998 Elsevier Science S.A. All rights reserved.